Relation between apoE gene polymorphism and coronary artery disease in South East and East Asian Countries - Ibrahim, Wisam Nabeel; Aladzemi, Farah Wahida; Muhammad Musa, Nur Ashikin; Nik Ahmad, Nik Nur Fatnoon; Abdullah, Nor Zamzila; A.Talib, Norlelawati (Science Alert, 2017)
Background and objective: Apolipoprotein E (apoE) is a polymorphic protein with vital antioxidant and anti-atherosclerotic effects. Three apoE isoforms exist due to polymorphisms in its gene causing disturbances of lipoproteins metabolism and a probability to develop cardiovascular diseases. The aim of this study was to assess the association between apoE gene polymorphism and coronary artery disease (CAD) in a Malaysian population sample and to integrate the study findings with other studies to increase the power of the study sample and to make a better understanding about the association between apoE gene polymorphism and CAD in south east & East Asian countries. Methods: The study involved 185 patients with CAD attending HTAA hospital Kuantan, Pahang with 188 unrelated healthy control participants. ApoE gene polymorphism was determined in the participants using polymerase chain reaction – restriction fragment length polymorphism (PCR-RFLP) assay and was validated using direct nucleotide sequencing. SPSS software version 19 and Chi-squared test was used for determination of allele and genotypes association with CAD. Binary logistic regression analysis of apoE genotypes, gender, ethnicity, age, blood pressure, and lipid profile was used to predict probability of developing CAD. In addition, meta-analysis was conducted using Review Manager (Version 5.3.). Results: the preliminary data has shown a non-significant association between apoE genotypes or alleles and CAD. Nevertheless, binary logistic regression analysis has shown a significant association between E3E4 genotype, high blood pressure, male gender & old age as dependant risk factors in the prediction for having CAD. The meta-analysis of studies in Southeast Asia and East Asia region had shown that carriers of the E4 allele are significantly at higher risk to develop CAD [p<0.0001; OR=1.51 (1.24, 1.83) CI=95%; I2=68%]. Conclusion: This study provides an evidence of increased risk to develop CAD among carriers of E4 allele specially if accompanied with high blood pressure, old age with male gender.